SOCIAL NETWORK ANALYSIS: GASTRODIPLOMASI MASAKAN TRADISIONAL INDONESIA MELALUI YOUTUBE PERIODE 2023-2024 - Ardi, Andre; Saguna, Muhammad Daffa (Moestopo Journal of International Relations (MJIR), 2025)
The purpose of this study is to analyze the response to gastrodiplomacy carried out by the Indonesian government through Youtube. The method used in this study is a descriptive qualitative method with data collection techniques obtained through the help of python tools. The theory used in this study is gastrodiplomacy, with the theory of social network analysis. The results of this study are the ineffectiveness of the strategy carried out by the government in promoting Indonesian gastrodiplomacy through Youtube, because there is still a lack of government actors who carry out gastrodiplomacy through Youtube. As well as the lack of recognition from non-state actors regarding this.